Generation of Pmel‐dependent conditional and inducible Cre‐driver mouse line for melanocytic‐targeted gene manipulation. (19th December 2022) - Nasrin, Morsheda; Ahmed, Osama; Han, Xujun; Nojebuzzaman, Md; Abo‐Ahmed, Ahmed I.; Yazawa, Shigenobu; Osawa, Masatake
Abstract: Conditional and inducible gene targeting using Cre/ loxP ‐mediated recombination is a powerful reverse genetics approach used to study spatiotemporal gene functions in specified cell types. To enable temporal gene manipulation in the melanocyte lineage, we established a novel inducible Cre‐driver mouse line by targeting an all‐in‐one tetracycline/doxycycline (Dox)‐inducible Cre expression cassette into the Pmel locus ( Pmel P2A‐TetON3G‐TRE3G‐iCre ), a gene locus preferentially expressed in pigment cells. By crossing these Cre‐driver mice with a strong Cre‐reporter mouse line, Gt(ROSA)26Sor tm9(CAG‐tdTomato)Hze, we show the effectiveness of the Pmel P2A‐TetON3G‐TRE3G‐iCre mouse line in facilitating Dox‐inducible Cre/ loxP recombination in a wide variety of pigment cell lineages including hair follicle melanocytes and their stem cells. Furthermore, to demonstrate proof of concept, we ablated Notch signaling postnatally in the Pmel P2A‐TetON3G‐TRE3G‐iCre mice. In agreement with the previously reported phenotype, induced ablation of Notch signaling in the melanocyte lineage resulted in premature hair graying, demonstrating the utility of the Pmel P2A‐TetON3G‐TRE3G‐iCre allele. Therefore, the Pmel P2A‐TetON3G‐TRE3G‐iCre mouse line is suitable for assessing gene functions in melanocytes using an in vivo inducible reverse genetics approach. Furthermore, we unexpectedly identified previously unrecognized PMEL‐expressing cells in non‐pigmentary organs in the mice, suggesting unanticipated functions of PMEL other than melanosome formation.